Thunder: A Design Process to Build Emotionally Engaging Music Visualizations - Nunes, Caio; Reinbold, Isabelle; Castro, Mariana; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Music's profound emotional impact extends beyond traditional listening experiences, playing a critical role in shaping user engagement in entertainment contexts, including digital games. Music visualizations -- graphical representations of musical elements such as rhythm, melody, and harmony -- are becoming increasingly significant for enriching emotional depth in these contexts. Despite the potential of music to enhance digital media experiences, there remains a gap in the intentional integration of musical visualizations with specific emotional narratives. In this paper, we propose Thunder, a design process for creating musical visualizations that prioritize conveying the emotional communication of music. Our approach builds on an existing method for rapid prototyping of animated musical visualizations and comprises four iterative phases. By applying this process in creating two music visualizations, we demonstrate that our process aligns closely with the designed emotional content of the music. The results showed that our alternative visualizations effectively communicated intended negative emotions, such as "sadness" and "shame", and were well-received by the public, highlighting the importance of synchronized visual and musical elements. With this work, we hope to offer valuable insights for game designers and entertainment app developers, providing a comprehensive design process for crafting musical visualization experiences that emphasize the emotional richness of music and pave the way for more immersive and emotionally resonant digital media experiences.